Membangun Karakter Mulia pada Anak Perspektif Kewirausahaan - Ita Nurcholifah (PSGA LP2M IAIN Pontianak, 2015)
The advanced growth especially on economic sector is an important matter in Indonesia nowadays. The effective booster to develop the nation’s economic is to expand the job emplyment that the societies have a powerful purchasing. Furthermore, the potential matter to create more chances for people to work is to duplicate more entrepreneurs in this country. Besides, it should start from an early age by building entrepreneurial character in children. To develop the entrepreneurial character there are several ways could be taken: First, build the self-confidence of children. Second, emphasize the hard-work desire or the willingness to be more active. Third, evolve their self-esteem that they are able to take a control of their own life. Forth, develop the conviction behavior or Istiqomah. Fifth, keep the precision or accuracy. Sixth, build the creative mindset. Seventh, help the children to solve their problems. And the last but not least, acquire the objective attitude of seeing or judging anything. Moreover, building the entrepreneurial character in children by giving them a good education, whether at home or family environment, social environment or community and school, should firstly promote the process of developing the entrepreneurial character itself. Likewise, to develop the entrepreneurial character should be done in precise and accurate ways so that the efforts to build the entrepreneurial character in children are not futile. Meanwhile, an attempt is made by describing it repeatedly and continuously, but it also needs the participation of parents at home, community leaders in the society, and also a teacher at school, in order to position themselves as educators who tend to give guidance and direction positively, rather than coercing the will of the children, especially in entrepreneurial character pinned on them. To conclude, by prioritizing the sincerity and gentleness learning ways, will certainly affect the children strongly.